KARAKTERISTIK ORGANOLEPTIK DODOL UBI JALAR (Ipomoea batatas L.) TERHADAP DODOL BUAH-BUAHAN - Deny Utomo (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
Sweet potato is one of the most important economic plants in the world, because it is rich in antioxidants. Processing sweet potatoes into dodol can increase the economic value of plants to food security, nutrition, increase in income and increase the welfare of farmers The purpose of this study was to determine the organoleptic characteristics of dodol products in three flavors. Organoleptic test using the Friedman Test with α = 0.05 and determining the best treatment using the index of effectiveness. The results showed that the best organoleptic test was obtained from sweet potato dodol products with a product value of 0.610 with a mean value of panelists' preference for taste of 4.40; color of 3.92 and aroma of 2.48.